Biotransformation and kinetics of selected benzimidazole synthetic opioids in human hepatocytes - Jadhav, Gajanan R.; Fasinu, Pius S. (Frontiers in Pharmacology, 2025)
Background/ObjectivesThe reemergence of 2-benzylbenzimidazole opioids, also called nitazenes, in the illicit drug market constitutes a serious threat to public health. One of the major challenges in handling exposures and managing intoxications in humans is the poor understanding of the kinetics and biotransformation pathways of these drugs. Although the scheduled status of nitazenes limits interventional clinical studies in humans, liver-based in vitro studies can provide insights into their metabolism and pharmacokinetics.MethodsThree nitazene analogs–butonitazene, isotonitazene, and protonitazene—were incubated in primary human hepatocytes. The depletion rate was profiled against time for metabolic kinetic analysis. Qualitative and quantitative analyses of the incubates were conducted using liquid chromatography–high-resolution tandem mass spectrometry.ResultsAll three analogs were rapidly metabolized in hepatocytes, with intrinsic clearance values of 2.4, 3.0, and 3.9 mL/min/g liver for butonitazene, isotonitazene, and protonitazene, respectively, yielding products of multiple metabolic reactions, including hydroxylation, N-dealkylation, glucuronidation, and acetylation. The extrapolated in vivo clearance [(mL/min)/kg body mass] values of butonitazene, isotonitazene, and protonitazene were 14.4, 15.2, and 16, respectively, compared to 15.5 and 18 for 7-hydroxycoumarin and testosterone, respectively.ConclusionNitazenes are susceptible to hepatic metabolism through hydroxylation, N-dealkylation, and conjugation. The extrapolated in vivo metabolic clearance is similar to that of 7-hydroxycoumarin and testosterone. For practical purposes, these findings can provide useful estimations in clinical toxicology and forensic pathology.